Particle Radiation-Induced Nontargeted Effects in Bone-Marrow-Derived Endothelial Progenitor Cells - Sharath P. Sasi; Daniel Park; Sujatha Muralidharan; Justin Wage; Albert Kiladjian; Jillian Onufrak; Heiko Enderling; Xinhua Yan; David A. Goukassian (Stem Cells International)
Bone-marrow- (BM-) derived endothelial progenitor cells (EPCs) are critical for endothelial cell maintenance and repair. During future space exploration missions astronauts will be exposed to space irradiation (IR) composed of a spectrum of low-fluence protons (1H) and high charge and energy (HZE) nuclei (e.g., iron-56Fe) for extended time. How the space-type IR affects BM-EPCs is limited. In media transfer experiments in vitro we studied nontargeted effects induced by 1H- and 56Fe-IR conditioned medium (CM), which showed significant increase in the number of p-H2AX foci in nonirradiated EPCs between 2 and 24 h. A 2–15-fold increase in the levels of various cytokines and chemokines was observed in both types of IR-CM at 24 h. Ex vivo analysis of BM-EPCs from single, low-dose, full-body 1H- and 56Fe-IR mice demonstrated a cyclical (early 5–24 h and delayed 28 days) increase in apoptosis. This early increase in BM-EPC apoptosis may be the effect of direct IR exposure, whereas late increase in apoptosis could be a result of nontargeted effects (NTE) in the cells that were not traversed by IR directly. Identifying the role of specific cytokines responsible for IR-induced NTE and inhibiting such NTE may prevent long-term and cyclical loss of stem and progenitors cells in the BM milieu.